Craniomandibular osteopathy in a crosbred dog - Chilón-Cornejo, Vicente (2020)
It is presented the case of a 9-month-old canine patient, of an undefined breed, with decreased feed intake and increased size of the ventral part of the mandible. Radiographic examination showed bilateral and ventral bone proliferation of the mandibular body with increased radiodensity in this area. The lesion was compatible with craniomandibular osteopathy, a rare disease of unknown etiology that affects young dogs and is usually self-limiting and has a favourable prognosis.